A pixel space method for testing dipole modulation in the CMB polarization. Issue 3 (3rd January 2020) - Ghosh, Shamik; Jain, Pankaj
ABSTRACT: We introduce a pixel space method to detect dipole modulation or hemispherical power asymmetry in the cosmic microwave background (CMB) polarization. The method relies on the use of squared total polarized flux whose ensemble average picks up a dipole due to the dipole modulation in the CMB polarization. The method is useful since it can be easily applied to partial sky. We define several statistics to characterize the amplitude of the detected signal. Through simulations, we show that the method can be used to reliably extract the signal at a 2.7σ level or higher in future CORE-like missions, assuming that the signal is present in the CMB polarization at the level detected by the Planck mission in the CMB temperature. An application of the method to the 2018 Planck data does not detect a significant effect, when taking into account the presence of correlated detector noise and residual systematics in the data. Using the Full Focal Plane 10, we find the presence of a very strong bias that might be masking any real effect.